2016
DOI: 10.1007/s00259-016-3433-2
|View full text |Cite
|
Sign up to set email alerts
|

TLG-S criteria are superior to both EORTC and PERCIST for predicting outcomes in patients with metastatic lung adenocarcinoma treated with erlotinib

Abstract: TLG-S criteria may be of greater help in predicting survival outcomes than other forms of assessment. Bone flares, which can interfere with the interpretation of treatment response based on PERCIST criteria, are not uncommon in patients with metastatic lung adenocarcinoma treated with erlotinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
1
20
0
1
Order By: Relevance
“…We found a strong correlation between MLV and SUV mean (r = 0.90); this result is probably due to the few patients included in the study. Our result is consistent with observations in oncology, with some studies suggesting TLG as a better predictor of outcomes in patients with lung or cervical cancer [17, 25]. We found MLV independently associated with prognosis, like TLG, so the volume of the lung with an altered uptake may be more informative to assess prognosis than the mean SUV in this volume.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found a strong correlation between MLV and SUV mean (r = 0.90); this result is probably due to the few patients included in the study. Our result is consistent with observations in oncology, with some studies suggesting TLG as a better predictor of outcomes in patients with lung or cervical cancer [17, 25]. We found MLV independently associated with prognosis, like TLG, so the volume of the lung with an altered uptake may be more informative to assess prognosis than the mean SUV in this volume.…”
Section: Discussionsupporting
confidence: 92%
“…TLG could be better than SUV mean or SUV max as a prognostic marker because it accounts for intracellular glucose accumulation within the total volume of all regions of interest [16]. Recently, TLG was found to predict overall survival in patients with liver colorectal metastases and those with lung cancer treated with erlotinib [16, 17]. Recently, one study demonstrated the prognostic value of dual-time-point [ 18 F]FDG PET for IPF [18].…”
Section: Introductionmentioning
confidence: 99%
“…Using PERCIST criteria, patients are generally classified as complete metabolic responders (CMR; complete resolution of tumor (18F)FDG uptake), partial metabolic responders (PMR; reduction of a minimum of 30% in target lesion uptake), progressive metabolic disease (PMD; increase of a minimum of 30% in target lesion uptake or presentation of a new lesion), and stable metabolic disease (not CMR, PMR, or PMD) 6 7. Total lesion glycolysis using a systematic approach is a relatively new method measuring response by PET, and some studies have suggested that it may be superior to PERCIST and EORTC methods 29 31 32…”
Section: Discussionmentioning
confidence: 99%
“…Several exploratory parameters mentioned in PERCIST look at both the SUL and the volume of the tumor, but these parameters require further validation. Total lesion glycolysis, the product of the mean SUL and the metabolic volume, showed predictive or prognostic values in cancers of the head and neck [10], lung [11], and uterus [12] to list just some, and in pancreas neuroendocrine tumors [13]. Simple product of volume and metabolic activity may not be the most accurate solution, and recently, a new metric was proposed that incorporates the commonly utilized metrics of SUV, metabolic tumor volume, and total lesion glycolysis into a single parameter [14].…”
Section: Performing Percistmentioning
confidence: 99%